Dental implants in patients with osteoporosis: a systematic review with meta-analysis - de Medeiros, F. C.F.L.; Kudo, G. A.H.; Leme, B. G.; Saraiva, P. P.; Verri, F. R. [UNESP]; Honório, H. M.; Pellizzer, E. P. [UNESP]; Santiago Junior, J. F. (Elsevier, 2018)
There is currently no consensus regarding the survival rate of osseointegrated implants in patients with osteoporosis. A systematic review with meta-analysis was performed to evaluate the survival rate of implants in such patients. The PubMed/MEDLINE, Web of Science, Cochrane Library, and SciELO databases were used to identify articles published up to September 2016. The systematic review was performed in accordance with PRISMA/PICO requirements and the risk of bias was assessed (Australian National Health and Medical Research Council scale). The relative risk (RR) of implant failure and mean marginal bone loss were analyzed within a 95% confidence interval (CI). Fifteen studies involving 8859 patients and 29,798 implants were included. The main outcome of the meta-analysis indicated that there was no difference in implant survival rate between patients with and without osteoporosis, either at the implant level (RR 1.39, 95% CI 0.93–2.08; P = 0.11) or at the patient level (RR 0.98, 95% CI 0.50–1.89; P = 0.94). However, the meta-analysis for the secondary outcome revealed a significant difference in marginal bone loss around implants between patients with and without osteoporosis (0.18 mm, 95% CI 0.05–0.30, P = 0.005). Data heterogeneity was low. An increase in peri-implant bone loss was observed in the osteoporosis group. Randomized and controlled clinical studies should be conducted to analyze possible biases.
Keywords: dental implants; marginal bone loss; meta-analysis; osteoporosis; review; survival rate